Strategi Pemasaran Industri Rumah Tangga Gula Aren di Kota Tomohon Marketing Strategy Home Industry of palm sugar in Tomohon - Jeane D Kaunang (COCOS, 2012)
ABSTRACT This research, aimed at determining alternative marketing strategies especially the marketing mix for home industry of palm sugar in Tomohon. The method of analysis used are the SWOT (Strengths, Weaknesses, Opportunities, Threats) and SPACE (Stategic Position and Action Evaluation). The results show that the home industry of palm sugar has strengths: product quality is good, as well as the availability of labors and natural resources, and capital required is relatively small. While weakness its are the packaging process of products produced still wears banana leaves and seems unattractive, not having brand and product labels, the promotions which is still not optimal, as well as long distribution channels and price information that are still lacking. Opportunities that need to be explored in home industries of palm sugar in Tomohon consist of  technological developments, the opening of export markets, partnership with food companies and changes in population. While threats encountered are changes of the consumer tastes and the emergence of similar products from other regions. The marketing position of palm sugar in home industries Tomohon is located in quadrant I. The strategy adopted in the marketing of this home industries has opportunity and strength in such a way that it can take advantage of existing opportunities. Appropriate strategy in this condition is to support an aggressive growth policy (Growth Oriented Strategy). From this research, it can be concluded that alternative marketing strategies described in obtaining the marketing mix through the matrix of SWOT (strengths, weaknesses, opportunities, threats) are as follow : the improvement of the  product  quality with packaging that makes it higienic and more attractive than other similar products, the determination of price by cost-oriented, promotion by making brochures through cooperation with the department of tourism and hospitality or the promotion via the Internet, establishing business partnerships with companies of food / beverage and supermarket, the distribution of product by expanding marketing using networking technology. And for the suggestions are to build a self production community  such as Village Unit Cooperation (KUD) to help the direct marketing of palm sugar and the increasing of the quality of human resource the home industrial entrepreneurs of palm sugar in Tomohon through integrated training both internal training from relevant agencies, as well as bringing marketing professionals or academic trainers by the government Tomohon especially Department of Industry and Trade. Keywords : Marketing Strategy, Home Industry